2018
DOI: 10.12783/dtcse/mso2018/20523
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Energy Absorbing Structure Inspired by Energy Harvesting Device

Abstract: An auxetic structure, exhibiting Negative Poisson's Ratio (NPR) effect, is different from a conventional structure due to its special properties, including indentation resistance, shear resistance, and sound absorption. The auxetic structure gets expanded when it is stretched, or becomes shrunk when it is compressed. Inspired by authors' previous research on design optimization of energy harvesting device (Piezoelectric Flex Transducer) scavenging biokinetic energy from human walking, a novel NPR structure is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Also, Yang [26] reported that negative Poisson's ratio material has good ability of energy absorption according to numerical results in its study about structural response of a negative Poisson's ratio structure with regular reentrant cell shape under the rigid wall crushing. Furthermore, Dong [27] mentions about better ability to absorb impact energy as well as increase structural strength makes NPR structures outperform the conventional structures in the various engineering applications when integrated with 3D printing technology.…”
Section: Auxetic Behaviour and Stress Resultsmentioning
confidence: 99%
“…Also, Yang [26] reported that negative Poisson's ratio material has good ability of energy absorption according to numerical results in its study about structural response of a negative Poisson's ratio structure with regular reentrant cell shape under the rigid wall crushing. Furthermore, Dong [27] mentions about better ability to absorb impact energy as well as increase structural strength makes NPR structures outperform the conventional structures in the various engineering applications when integrated with 3D printing technology.…”
Section: Auxetic Behaviour and Stress Resultsmentioning
confidence: 99%